The Knowledge Management Processes at Different Stages of Group Development - Pinto, Ana (2018)
Based on a developmental approach, this study intended to analyze the extent to which the diff erent stages of group development diff er regarding the use of knowledge management processes. The sample comprised 211 teams belonging to a Portuguese military organization. In order to test the hypotheses a multivariate analysis of variance was conducted. The results showed that more mature and cooperative groups (Restructuring/Realization phase) apply to a greater degree the processes of knowledge management, while groups in which there is high intragroup competition and in which members try to “gain power” among themselves (Reframing phase), apply these processes to a lesser degree.